2018
DOI: 10.1037/ocp0000061
|View full text |Cite
|
Sign up to set email alerts
|

Defeating abusive supervision: Training supervisors to support subordinates.

Abstract: Although much is known about the antecedents and consequences of abusive supervision, scant attention has been paid to investigating procedures to reduce its frequency. We conducted a quasiexperiment to examine the effects of supervisor support training on subordinate perceptions of abusive supervision and supervisor support. Supervisors (n = 23) in 4 restaurants were trained in 4 supportive supervision strategies (benevolence, sincerity, fairness, and experiential processing) during 4 2-hr sessions over a per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(77 citation statements)
references
References 92 publications
1
76
0
Order By: Relevance
“…Alternatively, 360° review system for the managers may serve the same purpose. In addition, organizations may reduce abusive supervision by training their leaders in supportive supervision characterized by benevolence, sincerity, fairness, and mindfulness (Gonzalez‐Morales, Kernan, Becker, & Eisenberger, ). Gonzalez‐Morales et al.’s study found that managers who attended four 2‐hr training sessions on supportive supervision were rated by their subordinates nine months later as exhibiting significantly lower levels of abusive supervision.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, 360° review system for the managers may serve the same purpose. In addition, organizations may reduce abusive supervision by training their leaders in supportive supervision characterized by benevolence, sincerity, fairness, and mindfulness (Gonzalez‐Morales, Kernan, Becker, & Eisenberger, ). Gonzalez‐Morales et al.’s study found that managers who attended four 2‐hr training sessions on supportive supervision were rated by their subordinates nine months later as exhibiting significantly lower levels of abusive supervision.…”
Section: Discussionmentioning
confidence: 99%
“…The finding of this study reveal that abusive supervision in the workplace can deteriorate the perceived trust-in-supervisor, which eventually affects the tendency of cooperation of frontline employees to supervisors. Hence, in this regard, there is a need to formulate organizational policies that are based on organization-wide zero tolerance against abusive behaviors [78,79], which lead to sustainable employment relationships. Moreover, managers are also advised to improve the selection and recruitment process of supervisors in order to curtail the abusive supervision in the workplaces.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…To take surface acting prevention one step further, managers and practitioners should show concern for the extent to which their employees feel supported by their organizations and supervisors and foster these perceptions. Recently, Gonzalez-Morales, Kernan, Becker, and Eisenberger (2016) provided evidence for the effectiveness of a brief supervisor support training program including four strategies (i.e., benevolence, sincerity, fairness, and experiential processing). Among other ways to achieve this objective, top management might promote a supportive culture within their organization, for instance, by providing to employees the resources they need to perform they job effectively, by providing assurance of security during stressful times, and by promoting justice and fairness in the way policies are implemented and rewards distributed (Eisenberger & Stinglhamber, 2011).…”
Section: Practical Implications and Conclusionmentioning
confidence: 99%